The national element in the development of fiscal theory - Kayaalp, Orhan (Palgrave Macmillan, 2004)
Price theory has provided solutions to myriad problems affecting society without invoking any precepts beyond those encapsulated in the standard economic postulate. Fiscal theory, meanwhile, has been closely attentive to the political, sociological and historical circumstances that bear upon the fiscal act. This methodological duality has resulted in the development of fiscal theory in line with the political culture espoused by its originator, usually the one prevailing at home. Thus emerges the need for an analysis of the evolution of fiscal thought along national lines.